Flood hazard modelling using HEC-RAS in the Pathariya Khola, Far-western Nepal (Journal of Nepal Geological Society, 2023)
Flood hazards are a common problem in flat-lying areas, particularly in southern Nepal due to heavy precipitation and the consequent large transportation of sediments from hilly regions. Bank erosion, flooding, inundation, and sedimentation are the major problems in the plain area of the Kailali District along the riverbanks of Pathariya Khola, which is located on the southern flanks of the Churia Range. The study has been focused on flood hazards and vulnerability evaluation. The river discharge was calculated by WECS/DHM method and flood frequency in various return periods was analysed using HEC-RAS, RAS-Mapper, and geographic information system (GIS) for hazard modelling to delineate the flood-prone areas. The flood hazard zones were categorized as moderate (26.29%), high (39.59%), and very high (34.12%) based on the computed water depths of peak floods. The agricultural land is the most vulnerable to flooding followed by built-up areas. The results have revealed that the flood hazard areas are ever-expanding with the increased discharge levels of different return periods.